THE EFFECT OF POPULATION SIZE, HUMAN DEVELOPMENT INDEX, AND FOREIGN DIRECT INVESTMENT ON ECONOMIC GROWTH IN TABANAN REGENCY - Ni Made Dewi Puspita Sari; Ida Bagus Putu Purbadharmaja (CV. Adiba Aisha Amira, 2025)
Economic growth is an important indicator in measuring the development performance of a region. Tabanan Regency experienced fluctuations in the rate of economic growth despite an increase in population, Human Development Index (HDI), and Foreign Direct Investment (FDI). This study aims to analyze the effect of population, HDI, and FDI on economic growth in Tabanan Regency for the period 2011-2024, both simultaneously and partially. The approach used in this study is a quantitative approach with multiple linear regression analysis based on time series data. The results of the analysis showed that simultaneously the variables of population, HDI, and FDI had a significant effect. Partially, population has a negative and significant effect on economic growth in Tabanan Regency, while HDI and FDI have a positive but insignificant effect on economic growth in Tabanan Regency. The results of this study emphasize the importance of the government's role in expanding employment opportunities through investment in various economic sectors, as well as simplifying business licensing to encourage labor force participation in Tabanan Regency. The government can also expand access to education and improve the transparency and consistency of regulations to reduce uncertainty and increase foreign investor confidence.